The practice of 'educational accompaniment' from tutoring in grieving situations - Agustín de la Herrán Gascón; Mar Cortina Selva (Tendencias Pedagógicas, 2015)
This article is continuation of an work initiated in 1998 and directed to the enrichment of the formation of the teaching staff from the Didactics and the Educative Direction, that altogether has come to denominate “Education for the Death” and “Didactics of Death” (A. de la Herrán el al., 1999; A. de la Herrán, y M. Cortina, 2006). The authors, make specific one methodology of paliative didactic intervention, contrasted actually with positive evaluation, that is tried to objetive and to put under debate to be developed by the tutor. For a greater didactic potentiality, it has been decided on its presentation from several examples, stopping to us in each one of them in its description, its interpretation and the performance recommended according to the proposed model, that has denominated `educative support’. For its integral understanding it is recommended, therefore, to review the totality of the cases. The most outstanding aspect of this model of tutorial intervention is indeed that it sets out to the didactic tutor- and not to the orientation one- like `accompanying’. In principle, is the tutor the tutor the person with affective bond, that better knows the student and who interacts more with the family. Therefore, except for exceptions (indicating of W.C. Kroen, 2002), tutor has to be the person who, with suitable formation, better can carry out from her orientation function ‘educative support’.